2003
DOI: 10.1021/es030362h
|View full text |Cite
|
Sign up to set email alerts
|

Global Distribution of Radionuclides (137Cs and40K) in Marine Mammals

Abstract: Concentrations of anthropogenic radionuclides were measured in the muscle of marine mammals collected from various locations all over the world, and the global distribution of 137Cs in marine mammals was investigated. 40K was detected in all the specimens of marine mammals with no apparent difference between regions. An anthropogenic radionuclide, 137Cs, was detected in most of the species of marine mammals. With regard to the worldwide distribution of 137Cs, the highest concentration was noticed in the U.K. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 29 publications
4
23
0
5
Order By: Relevance
“…From these areas harbour porpoises (Phocoena phocoena) had a mean 137 Cs activity in muscle tissue of 6.9 Bq/kg w.w. (N = 19, range from undetectable to 66.6 Bq/kg w.w.) (Watson et al, 1999). The second highest values of 137 Cs reported are from Baikal seals (Phoca sibirica) with a mean muscle value of 14.0 F 2.0 (SD) Bq/kg w.w. (N = 5, range from 12.0-17.0 Bq/kg w.w.) (Yoshitome et al, 2003). Values of 137 Cs, comparable to those reported by Watson et al (1999) and Yoshitome et al (2003) were also reported from harbour porpoises collected in the Black Sea in 1993 (N = 5, mean = 9.0 F 2.1 (SD) Bq/kg w.w.) (Kanivets et al, 1999).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…From these areas harbour porpoises (Phocoena phocoena) had a mean 137 Cs activity in muscle tissue of 6.9 Bq/kg w.w. (N = 19, range from undetectable to 66.6 Bq/kg w.w.) (Watson et al, 1999). The second highest values of 137 Cs reported are from Baikal seals (Phoca sibirica) with a mean muscle value of 14.0 F 2.0 (SD) Bq/kg w.w. (N = 5, range from 12.0-17.0 Bq/kg w.w.) (Yoshitome et al, 2003). Values of 137 Cs, comparable to those reported by Watson et al (1999) and Yoshitome et al (2003) were also reported from harbour porpoises collected in the Black Sea in 1993 (N = 5, mean = 9.0 F 2.1 (SD) Bq/kg w.w.) (Kanivets et al, 1999).…”
Section: Discussionsupporting
confidence: 83%
“…The second highest values of 137 Cs reported are from Baikal seals (Phoca sibirica) with a mean muscle value of 14.0 F 2.0 (SD) Bq/kg w.w. (N = 5, range from 12.0-17.0 Bq/kg w.w.) (Yoshitome et al, 2003). Values of 137 Cs, comparable to those reported by Watson et al (1999) and Yoshitome et al (2003) were also reported from harbour porpoises collected in the Black Sea in 1993 (N = 5, mean = 9.0 F 2.1 (SD) Bq/kg w.w.) (Kanivets et al, 1999). In the Eastern Tropical Pacific specific activities in three dolphin species were above detection limits in samples from the late 1970s and early 1980s.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations